CRIMINOLOGICAL ANALYSIS OF CYBERBULLYING CRIMES OCCURRING ON SOCIAL MEDIA (STUDY OF COMMENTS ON THE TIKTOK ACCOUNT ELYNAWA21) - Harefa, Safaruddin; Ismawati, Sri; Hertini, Mega Fitri (Faculty of Law Sriwijaya University, 2024)
This research aims to examine the phenomenon of crime in the social media landscape, particularly cyberbullying, which has become increasingly prevalent. The primary focus is on how the development of information and communication technology has facilitated bullying on social media platforms. Utilizing the social control theory by Travis Hirschi and Michael Gottfredson, this study emphasizes that individuals with weak attachments to social institutions, such as family, school, or community, are more susceptible to engaging in criminal behavior, including cyberbullying. This study analyzes comments targeting the physical appearance of individuals, where the lack of social supervision and weak self-control are identified as key factors contributing to cyberbullying behavior. Additionally, a low awareness of legal frameworks, such as the ITE Law governing online harassment, further intensifies this issue. The novelty of this research lies in applying social control theory within the context of cyberbullying on social media, highlighting the importance of strengthening social bonds and implementing social control mechanisms as preventive strategies. The study also provides valuable insights into the need for more effective law enforcement and educational efforts to mitigate and address the rising cases of cyberbullying in the digital age.